Creating the 1831 Canadian Census Database. Issue 2 (3rd April 2019) - Cherkesly, Isabelle; Dillon, Lisa; Gagnon, Alain
Abstract: The 1831 census database is the newest addition to the series of 19th century Canadian census microdata available for social science research, thanks to a collaboration between the Programme de recherche en démographie historique (PRDH) and FamilySearch. This article presents the work undertaken to prepare this database and the main challenges encountered in the course of this work. While the data extracted from the 1831 census are an invaluable tool for demographic research, particularly on account of the agricultural and industrial questions included in this census, cleaning these data have required particular attention to the age-sex-marital status tallies of the household co-residents. Additional efforts were devoted to integrating missing data for Montréal's Notre-Dame parish and for other parishes.